How the coach-athlete relationship can fly or founder - Collins, D.; MacNamara, A. (Talent development: A practitioner guide, 2018)
This chapter examines the coach-athlete relationship within the talent development process. Recognising that the needs of the athlete will change as they progress along the pathway, this chapter explores good practice for coaches working with athletes at different stages of development and how they can support their development appropriately in light of developmental challenges from both within and outside the sporting environment. An argument is made for the importance of high-quality coaching, with a workforce equipped to work with, and empathetic towards, the needs of young athletes.